The INVITRO ANTICANCER ACTIVITY OF MEDICINAL PLANTS - kumar, Ajit (IJRDO-Journal of Applied Science, 2019)
ABSTRACT:Plant materials have been used for medical purposes in human life. Cancer diseases severely effect the human populations in worldwide. There is a constant challenge to find out the new therapies and drugs for treating cancer. The new focus is on finding anti cancer drugs with less side effects compared to current treatments such as chemotherapy. Historical use of plant materials might contain anticancer activities. This study evaluated three plant extracts on cancer cells. The essential oils extracts of Hedyotis corymbosa, Inula racemosa and Holostemma adakodien were studied against cancer cells. All the three plant extracts have shown dose dependent cancer cell killing activity.